Implementasi Pasal 2 Dan Pasal 5 Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) Terkait Marital Rape di Indonesia - Ave Agave Christina Situmorang; Sintong Arion Hutapea (Tirtayasa Journal of International Law, 2022)
ABSTRACT Articles 2 and 5 of CEDAW stipulate the obligation of the state to establish related arrangements for the elimination of all forms of discrimination against women. Indonesia has an obligation to establish regulations and protect victims in cases of marital rape. This is because the Criminal Code does not regulate marital rape. Marital rape is regulated in Law No. 23 of 2004 concerning the Elimination of Domestic Violence, but the law still creates many perceptions. This paper is a juridical study of the implementation of Article 2 and Article 5 of the Convention on The Elimination of All Forms of Discrimination against Women (CEDAW) by the Government of Indonesia in relation to Marital Rape. The research method used is a normative legal research method. The normative legal research method is a legal research method that focuses on library research. Normative legal research focuses on analyzing data such as legislation, legal theory, as well as legal research scientific works.Keywords; Woman; Marital Rape; CEDAW.ABSTRAKPasal 2 dan Pasal 5 CEDAW mengatur kewajiban negara untuk membentuk pengaturan terkait terhadap penghapusan segala bentuk diskrimansi terhadap perempuan. Indonesia memiliki kewajiban untuk membentuk peraturan-peraturan dan melindungi korban – korban dalam kasus marital rape. Hal tersebut dikarenakan KUHP belum mengatur terkait marital rape. Marital rape diatur dalam Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga, akan tetapi undang-undang tersebut masih menimbulkan banyak persepsi. Tulisan ini merupakan penelitian yang menelaah secara yuridis mengenai implementasi Pasal 2 dan Pasal 5 Convention on The Elimination of All Forms of Discrimination against Women (CEDAW) Oleh Pemerintah Indonesia Terkait dengan Marital Rape. Metode penelitian yang digunakan adalah metode penelitian hukum normatif. Metode penelitian hukum normatif merupakan metode penelitian hukum berfokus pada penelitian kepustakaan. Penelitian hukum normatif fokus pada pengkajian data seperti peraturan perundang-undangan, teori hukum, dan juga karya ilmiah penelitian hukum.Kata Kunci; Perempuan; Marital rape; CEDAW.